Immunoblotting confirmation that β-actin-PafA-Myc ligates 3 × Flag-TbN-PupE substrate to HA-AMOT. - Lin Xie (136792) (2025)
(A) Validation of the labeling efficiency of TbC-PupE and TbN-PupE on interacting proteins by PafA. (B) Immunoblotting confirming that actin-PafA-Myc ligates the 3 × Flag-TbN-PupE substrate onto exogenous AMOT-HA. 3 × Flag-TbN-PupE stably expressed cells were transfected with AMOT-HA alone, PafA-Myc&AMOT-HA, or actin-PafA-Myc&AMOT-HA. The red arrowhead indicates the molecular weight laddering of AMOT-HA after Flag-IP. (C) Split-TurboID between actin-Flag-TbN and HA-TbC-YAP1, AMOT-Flag-TbN and HA-TbC-YAP1. The red arrowheads indicate size of AMOT-Flag-TbN, and blue arrowheads indicate size of HA-TbC-YAP1, while asterisks represent non-specific bands. (TIF)